Kelayakan Finansial Proyek Investasi Pengebunan Jeruk Keprok Batu 55 Secara Monokultur di Wilayah Kabupaten Banyuwangi - Supriono, Agus; Atrianto, Jovi Lutvi; Faidah, Ainun; Kuntadi, Ebban Bagus; Hasanah, Julita (KUBIS, 2025)
The demand for imported tangerines, especially Mandarin tangerines, has continued to increase domestically over the years. However, there is also a local variety of tangerine whose appearance, flavor, and aroma are relatively similar to those of the Mandarin tangerine, and it is said to have great potential to become a strong competitor in the domestic market — the Batu 55 tangerine. The ideal environmental conditions for cultivating Batu 55 tangerines are in highland areas with altitudes ranging from 700 to 1,200 meters above sea level. Nevertheless, due to its promising market prospects, several farmers in lowland areas (below 700 meters above sea level), such as in Sembulung Village – Cluring District – Banyuwangi Regency – East Java Province, have begun to show interest in cultivating it as a monoculture crop. Since the cultivation is being developed in lowland areas, it is important to question its financial feasibility. Research results show that: (a) a monoculture Batu 55 tangerine plantation investment project per hectare in Banyuwangi Regency, with a planting distance of 5 x 5 meters, using seedlings propagated vegetatively (cuttings), an estimated economic lifespan of 16 years, base year set in 2011, and a discount rate/discount factor (df) of 9% per year, is considered financially feasible; (b) if there is a decrease in production quantity and average selling price by up to 30%, the investment project becomes financially infeasible; and (c) if operational variable costs increase by up to 30%, the investment project remains financially feasible.. Keywords: Banyuwangi, Batu 55, Feasible, Financial, Monoculture, Orange, Tangerines